Solitary extramedullary plasmacytoma of the lung with rapid transition to multiple myeloma : A rare case report and brief literature review - English Kevan; Leon Dianalyn De; Kaldas Sandra (Romanian Journal of Internal Medicine)
Solitary extramedullary plasmacytomas (SEPs) are disease entities characterized by the local proliferation of neoplastic plasma cells, representing less than 6% of plasma cell tumors. They typically produce monoclonal immunoglobulin and are usually found in the head, neck, and, less commonly, in the lungs. SEP, in rare instances, can transition to multiple myeloma (MM) with an estimated risk between 8 and 31%.